Humanitarian Logistics & Global Governance: A Portrait of International Cooperation between Indonesia and Timor Leste - Sukoco, Johan Bhimo; Araujo, Tolentino de; Kusumastuti, Dora; Fauziah, Luluk; Adjani, Allaydha Syafa (Universitas Diponegoro, 2022)
Humanitarian logistics becomes an interesting topic of study in logistic science. Nevertheless, researchers have not paid much attention to cross-country relations in reinforcing the humanitarian logistics. Meanwhile, Van Wassenhove (2006) states that responses from international aid agencies are needed to deal with humanity logistic reinforcement. This paper studies human logistics in relation to global governance, through a case study on the international cooperation between Indonesia and Timor Leste.This research used a descriptive qualitative method. This research used literature study, supported with secondary data from various reports, news on mass media, books, and scientific journals. The author elaborated these data sources and then analyzed and displayed data, and drew conclusion.The result of research shows that Indonesia and Timor Leste has good international cooperative relations in humanity field. This relation is established well through Indonesian Red Cross and Cruz Vermelha de Timor Leste (CVTL). These two neighboring countries have similar disaster typology, and thus need cooperation in disaster management. Further cooperation reinforcement will be needed in humanitarian logistics in these two countries in the future.